Global Trends In The Learning Process Of Pancasila And Citizenship Education In Schools - Daulay, Azizah Nur Khalisah; Hanifah, Hainun; Al Husna, Sakhi Nabila; Al Karim Rambe, Rahmansyah Fadlul (Pena Cendekia Insani, 2024)
This research discusses the global trend in Pancasila and citizenship education for democracy which has the potential to tremendously affect Pancasila and citizenship education in countries that adhere to constitutional democracy. Citizenship education certainly has implications for the learning process of citizenship education in schools (as a subject). The results of the study show that the global trend of citizenship education is evident in the vision and mission of Pancasila and citizenship education in Indonesia which is oriented towards the formation of good, intelligent and democratic citizens. The overall global trend has implications for the learning process of civics education at the school level, namely the components of objectives, materials, methods, media and sources, as well as evaluation of civics education learning.